Modal Budaya Dalam Tradisi Perencanaan - Sebayang, Asnita Frida (Center for Research and Community Services ITB, 2008)
One of the progresses that influence the development of planning theory is caltural dynamic. Planning cannot be separated from cultural dynamic since planning has systemic dimension towards uture view. This paper, therefore, is aimed to discuss cultural dimension as a capital that cannot be separated from planning theory whose interactions with economical functions are needed to achieving equilibrium between market rationality and social rationality. By elaborating the role of culture as a capital in planning tradition, it can be concluded that culture is a collective programming toward a decision tahen by a community. The tradition of social learning in planning theory can explain cultural interaction as part of learning process and can explain the problem of disparity between planning theory and practice through the concept of externality.